Impact of Psoriasis on Pregnancy Desire and Possible Consequences on Fertility - Burlando, Martina; Salvi, Ilaria; Poddine, Gabriele; Cozzani, Emanuele; Parodi, Aurora (Dermatology Practical & Conceptual, 2024)
Introduction: Approximately half of patients affected by psoriasis are women, and the management of female patients of childbearing age is an under-investigated topic. Some studies have shown a significant decrease in births in psoriatic patients, due to intimacy and pregnancy avoidance and to potential birth complications. Objectives: We sought to evaluate, in a cohort of female patients, data on reproductive health and compare them with similar data in the general population and assess the impact of psoriasis, especially genital psoriasis, on pregnancy desire, and the prevalence of psoriasis in children of patients with psoriasis. Methods: This retrospective observational study involved adult female patients with a diagnosis of psoriasis made during or before childbearing age. The enrolled patients were asked questions concerning fertility and previous pregnancies in relation to their dermatologic disease. Results: Of 100 women enrolled, 73 reported a history of pregnancy, for a total of 170 pregnancies. The average number of pregnancies to term and the average number of children per woman (1.2 ± 1) were lower than the national average. The percentage of miscarriages was 18.2%, higher than the national average, in particular, women with psoriatic arthritis had a greater percentage of miscarriages (27.4%). During the pregnancies, psoriasis was mainly stable (36.1%) or improved (29.2%), even though most patients (91.5%) did not follow any treatment. Conclusions: Psoriasis impacts pregnancy desire and course. The management of psoriasis in women of childbearing age is crucial to minimize its burden on this vulnerable population.